Ectopic pregnancy: a cause for maternal morbidity - B., Priyadarshini; R., Padmasri; T. L., Jnaneshwari; K. P., Sowmya; Bhatara, Urvashi; V., Hema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Despite the scientific and technological advances maternal morbidity and mortality continue to occur across the globe with regional variation. Ectopic pregnancy is one such cause which contributes to devastating fate of pregnant ladies. Over a period of time there have been variations in the incidence, cause, clinical presentation and management of ectopic pregnancy. The objective is to observe variations with respect to incidence, cause, clinical presentation and management of ectopic pregnancy Methods: The present study was a 1year prospective and 1 year retrospective study from Dec 2012 to Nov 2014 at a tertiary medical college in Karnataka. All diagnosed cases of ectopic pregnancy were enrolled in the study. Statistical methods employed in the present study were contingency table, chi-square test and contingency coefficient analysis (cross tabs procedure). Results: 38 cases were studied during two year period out of which 94.8% were tubal pregnancies, 2.6% each were cervical pregnancy and pregnancy in the rudimentary horn of the uterus. Maximum incidence of tubal gestation was noticed between the age group of 21-30 years (60.1%). 55.2% were nulliparous and 29% were multiparas. Commonest mode of termination was rupture in 57.9% of the cases; tubal abortion was seen with haemoperitoneum in 26.3% of the cases. Conclusions: Ectopic pregnancy remains a significant gynaecologic emergency, delay in diagnosis and treatment can be catastrophic, but early diagnosis and timely treatment can virtually eliminate need for surgical intervention.